The Effect of Cooperative Group Investigation Technique and Motivation towards The Eighth Grade Students’ Reading Comprehension At Junior High School Number 1 of Belitang - OKU Timur - Herlina Herlina (Universitas PGRI Palembang, 2013)
ABSTRACTThis study was conducted to solve the problems faced by the writer as the teacher of English at Junior High School Number 1 of Belitang OKU Timur. She result of the preliminary study at the eighth grade of Accounting Department showed that the students’ motivation and reading comprehension in English still low and did not meet the criteria of success. Furthermore, they had involvement to participate actively in motivation and reading comprehension. This study was conducted in experimental research to 64 students At Junior High School Number 1 of Belitang OKU Timur in the second semester of the academic year of 2012- 2013. It was took place for four months in twelve meetings and started from February to June 2013. There were some instruments to achieve the purpose ofstudy, namely: reading comprehension test that was included 40 questions in multiple choice form, and the questionnaire of motivation that was included 30 statements.Key Words: Group investigation, Motivation, and Reading Comprehension.